1992
DOI: 10.3109/10428199209049804
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Chronic Lymphocytic Leukaemia Cells to Interferon-α Generated Lymphokine Activated Killer Cells

Abstract: Recent studies have shown that, when used in early stage disease, interferon-alpha (IFN-alpha) can produce a fall in the number of malignant cells in the peripheral blood of patients with B-CLL. In this study, we investigated the effect of IFN-alpha on natural killer (NK) cell and lymphokine-activated cell (LAK) activity in patients with B-CLL. In vitro, IFN-alpha (500 U/ml for 18 hours) induced LAK activity in patients with B-CLL (27.7 +/- 9.9%, n = 20), and IL-2 (500 U/ml for 5 days) produced similar activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…Poor expression of CD69 was also observed on CD16 þ CD56 dim NK cells from CLL patients; this deficit could explain the previously reported reduction in NK cytotoxic activity in the absence of exogenous stimulation. 15,28 This relative NK-cell anergy could be due to the ability of CLL cells and their microenvironment to produce cytokines, such as IL-10, which suppress the proliferation of antigen-specific Th1 cells and downregulate co-stimulatory molecules on antigen-presenting cells. [29][30][31] Importantly, NK-cell function was perfectly recovered following activation.…”
Section: Discussionmentioning
confidence: 99%
“…Poor expression of CD69 was also observed on CD16 þ CD56 dim NK cells from CLL patients; this deficit could explain the previously reported reduction in NK cytotoxic activity in the absence of exogenous stimulation. 15,28 This relative NK-cell anergy could be due to the ability of CLL cells and their microenvironment to produce cytokines, such as IL-10, which suppress the proliferation of antigen-specific Th1 cells and downregulate co-stimulatory molecules on antigen-presenting cells. [29][30][31] Importantly, NK-cell function was perfectly recovered following activation.…”
Section: Discussionmentioning
confidence: 99%
“…29 The observation that NK activity is significantly reduced in peripheral blood of CLL patients as compared to healthy donors could argue for an NK cell dysfunction contributing to tumor cell accumulation in vivo. [16][17][18][19] Reasonably, then, increased numbers and/or activity of killer cells might be therapeutically beneficial for CLL, as it has been shown that NK cells have low cytotoxic capacity in B-CLL patients. [16][17][18][19] However, with all leukemic patients, autologous antileukemic effector cells are difficult to collect because of their limited number in the peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Reasonably, then, increased numbers and/or activity of killer cells might be therapeutically beneficial for CLL, as it has been shown that NK cells have low cytotoxic capacity in B-CLL patients. [16][17][18][19] However, with all leukemic patients, autologous antileukemic effector cells are difficult to collect because of their limited number in the peripheral blood. Previously, others studied expansion of NKT but not of NK cells from the peripheral blood of B-CLL patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations